Hot Topic: Title IV-E MSW Education and "Intent to Stay" in Public Child Welfare. Issue 1 (5th November 2018) - Carr, L Christian; Leung, Patrick; Cheung, Monit
Abstract: The 2018 proposed Family First Prevention Services Act suggests a change in the funding formula of Title IV-E of the Social Security Act—from entitlement to block grants. This study aimed to support the continuation of entitlement support based on the evidence that Title IV-E educational programs are effective in improving retention after the workers have obtained an MSW degree. Using a multigroup, multiple regression approach, this study analyzed secondary data collected from an e-survey sent to public child welfare (PCW) workers in a southern state. Data from 1, 025 workers compare "intent to stay" (ITS) factors between PCW workers who received and those who did not receive the Title IV-E MSW educational stipend. The main analysis was conducted using Mplus version 7.4, with R version 3.3.2 used for data screening. Findings indicate that Title IV-E–supported education moderates the strength of the following ITS factors: respect from coworkers, team cohesion, self-assessed skills in working with special needs clients, and holding an MSW degree. MSW holders expressed lower ITS levels unless they had received Title IV-E stipends. These results provide evidence that Title IV-E education could help retain MSW graduates in PCW.